Heritage genetics for adaptation to marginal soils in barley. (May 2023) - Schmidt, Sidsel Birkelund; Brown, Lawrie K.; Booth, Allan; Wishart, John; Hedley, Pete E.; Martin, Peter; Husted, Søren; George, Timothy S.; Russell, Joanne
Highlights: Growers need to produce increased crop yield to use resources more effectively and be resilient to abiotic stress and changing climates; however, current approaches are leading to maladaptation to stress. Bottlenecks in the selection of barley varieties have resulted in a reduction of genetic diversity that is obstructive to climate-smart agriculture. To reverse genetic erosion and identify novel sources of variation, we are re-examining and reintroducing crop landraces. Landscape genomics can add a new dimension by modelling potential adaptive responses to a specific environment or global climate change. In a conceptual model, we outline a targeted breeding programme connecting old cultivar collections with state-of-the-art gene discovery and phenotyping, necessary to provide new resources for future needs. Abstract: Future crops need to be sustainable in the face of climate change. Modern barley varieties have been bred for high productivity and quality; however, they have suffered considerable genetic erosion, losing crucial genetic diversity. This renders modern cultivars vulnerable to climate change and stressful environments. We highlight the potential to tailor crops to a specific environment by utilising diversity inherent in an adapted landrace population. Tapping into natural biodiversity, while incorporating information about local environmental and climatic conditions, allows targeting of key traits and genotypes, enabling crop production in marginal soils. We outline future directions for the utilisation of genetic resources maintained in landrace collections to support sustainable agriculture through germplasm development via the use of genomics technologies and big data.